Building Relational Marketing and Brand Image on Consumer Loyalty at Aroma Coffee Store - Hendro Priyono; Susi Indriyani (Management Department Universitas Islam Negeri Sumatera Utara, 2022)
The trend of growth in the number of coffee shops in 2021 is relatively increasing, but there is a phenomenon of a decline in coffee shop consumers; this occurs because consumers shift consumption from coffee shops to household consumption, where consumers choose to spend their money on consumption of primary needs. Efforts to attract the number of consumers during the pandemic need to be carried out more massively to build relationships between consumers and coffee shops and provide assurance that coffee shops also implement suitable health protocols in running their business. Efforts continue to be made by Kedai Kopi Aroma to attract consumer loyalty by providing live music and a beautiful night view to be enjoyed with friends or with family and also by advertising the place of business of the Aroma Coffee Shop both online and offline such as on social media. The writing of this thesis is whether relational marketing and brand image have a partial influence on consumer loyalty at the Aroma Coffee Shop. The type of research used is quantitative research with a sample of 98 respondents. Based on the study results, relational marketing and brand image have a partial influence on consumer loyalty at the Aroma Coffee Shop.Keywords: Image, loyalty, relational